Development of Interactive Multimedia for Learning of Isometry in Course of Geometry Transformation - Sakur, Sakur (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
Researchers are keen to develop interactive multimedia of web-based learning for topics advance isometry on courses of geometry transformation. Development of interactive multimedia learning using Microsoft Power Point, Adobe Reader, paint, and mobirise.net. Products that can be generated in this research are interactive multimedia to Students who follow courses of geometry transformations. The specifications of products packaged in Compact Disk (CD). Instruments for data collection form validation sheets about Learning Media and questionnaire for students. The results of the analysis of interactive multimedia learning validation shows very valid. The results of the analysis of responses shows that the practicalities of students well categorized. Aspects category to see a very good, well categorized presentation of the material aspects, and aspects of the program is very good category. The results of data analysis questionnaire for students found that the use of interactive multimedia web-based learning has been eligible practicalities so that it can be used in learning. Display interactive multimedia learning with animations very attractive, making the students easily understand the learning materials. In this development research, producing instructional CD which can then be used researchers to examine other aspects of learning and research.